Value of Orthostatic Hypotension as a Prognostic Bed-Side Test in Heart Failure - Rahman, Tarek M. A. (Scientific Research, 2012)
Background: Neurohumoral compensatory mechanisms play an important role in stabilizing the functional activity of patients with heart failure using the arms of autonomic nervous system. Orthostatic Hypotension (OH) is one of the most incapacitating symptoms of Cardiac Autonomic Dysfunction (CAD). OH can include sympathetic withdrawal which in turn leads to marked disability and deterioration of heart failure symptoms. Progressive Autonomic Dysfunction (AD) associated with progressive deterioration and impact on mortality of many diseases as hypertension, diabetes and other chronic diseases. The idea of using (OH) as a bed-side simple test expecting the risk of deterioration of cardiac function and furthermore on mortality open a gateway for preventive medicine and care to these group of patients. For more confidential prove, studying subjective and objective factors in heart failure patients became necessary to support these idea. Methods and Results: Sixty-Four patients with known history of heart failure were collected. All patients taking the fixed regiment of 4 drugs (diuretic, ACE inhibitor, Digitalis and B-blocker) in appropriate tolerated doses for two weeks prior to the study. History taking and all routine investigations were done for all patients. Grouping is based upon wither they have (OH) or not. Group-A found to have normal BP response to standing; they were 24 patients (18 male and 6 female) of mean Age (45 ± 8 years). Group-B discovered to have significant (OH) and was 22 patients (16 males and 6 females) of mean Age (43 ± 4 years). The first Clinical and Echocardiographic examination was done and considered as a base-line characteristic. Then, a Call-back after 6 months for follow-up and second visit examination is recorded. Furthermore, every patient was advised to report changes in his clinical symptoms in a note-book describing five main items to answer a questionnaire at the end of the study involves [times of admission to hospital, need for treatment modification, numbers of paroxysmal nocturnal dysnea, numbers of arrhythmic episodes and manifest lower limb edema]. At the end of the study, statistical methods are used to clarify the changes in their data and detect deterioration of cardiac functions by Echocardiographic results and their answers to the questionnaire. In the first visit, comparison of demographic, clinical and Echocardiographic data revealed no significant variations—odd values are excluded and the remaining 46 patients are then tested for their Bp response to standing and classified into two groups. Group-A (normal Bp response) and Group-B (having orthostatic hypotension). Group-A were 24 patients (18 male and 6 female) of mean Age (45 ± 8 years). Group-B were 22 patients (16 males and 6 females) of mean Age (43 ± 4 years). In the second visit (6-month later), divergence of data is observed and was statistically significant. Group-B was found to have a lower EF% and FS% (p = 0.01), a lower Dp/Dt (p = 0.01) and a higher Tie-Index and MR-jet area (p = 0.01). This means that, patients having orthostatic hypotension underwent significant deterioration of cardiac functions after a period of six-months. Indeed, the questionnaire proved frequent times of hospital admissions, paroxysmal nocturnal dysnea, need for treatment modification, arrhythmias and lower limb edema in group-B. Discussion: The present study conclude that, heart failure-patients having orthostatic hypotension experienced a significant deterioration of clinical condition and cardiac functions along a period of six-months which represent failure in their autonomic compensatory mechanisms and possible impact on their mortality. However, extended trials on mortality are needed to confirm this idea. Otherwise, we might use (OH) as a simple, rapid, bed-side tool to determine their prognosis and directing the physician attention to close care towards these subset of patients.
Keywords: Orthostatic; Hypotension; Heart Failure